2015
DOI: 10.1371/journal.pone.0145116
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNAs Involved in Reprogramming Acinar Cells into Insulin Producing Cells

Abstract: Reprogramming acinar cells into insulin producing cells using adenoviral (Ad)-mediated delivery of Pdx1, Ngn3 and MafA (PNM) is an innovative approach for the treatment of diabetes. Here, we aimed to investigate the molecular mechanisms involved in this process and in particular, the role of microRNAs. To this end, we performed a comparative study of acinar-to-β cell reprogramming efficiency in the rat acinar cell line AR42J and its subclone B13 after transduction with Ad-PNM. B13 cells were more efficiently r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…These miRNAs may be involved in the development of MetS. Previous studies have suggested that miR-137-3p may be associated with the production of insulin as well as the metabolism of lipids [ 21 , 22 ]. Ventriglia et al demonstrated that the expression of miR-409-3p was downregulated in the plasma samples of diabetic mice [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These miRNAs may be involved in the development of MetS. Previous studies have suggested that miR-137-3p may be associated with the production of insulin as well as the metabolism of lipids [ 21 , 22 ]. Ventriglia et al demonstrated that the expression of miR-409-3p was downregulated in the plasma samples of diabetic mice [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies indicated that miR‐210 was involved in cell reprogramming. For instance, miR‐210 was reported to be involved in the reprogramming of acinar cells into insulin‐producing cells (Teichenne et al, ), and modulating the EMT of ovarian cancer cells (Ding et al, ). Our results indicated that miR‐210 accelerated the dedifferentiation of Stro‐1 − /CD117 − non‐OSC cells into Stro‐1 + CD117 + OSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The observed upregulation of hsa-miR-135a suggests a mechanism that could, directly or indirectly, influence the development of renal fibrosis in individuals with diabetes. It has also been shown that hsa-miR-135a, among other miRNAs, is of importance for reprogramming acinar cells into insulin producing cells 34 , which suggests a therapeutic potential for this miRNA. Hsa-miR-135a is a pivotal miRNA in biogenesis and regulation in various forms of cancer 35 .…”
Section: Discussionmentioning
confidence: 99%